Perancangan Konten Media Sosial Sebagai Media Informasi dan Media Promosi di Graha Kita 18 - Elyanto, Yefta Novfensia; In Diana Sari, Ni Luh Desi; Larry Julianto, I Nyoman (AMARASI: JURNAL DESAIN KOMUNIKASI VISUAL, 2024)
Technology which always growing in the digital era has given people the ability to connect more easily through social media. Social media opens up opportunities for companies to communicate and promote their business through it to other people/audiences. One of the companies in Bali called Graha Kita 18, is a company engaged in home building needs, has utilized social media as their main promotional media to communicate and promote its products and services. The design of social media content at Graha Kita 18 is done through Instagram and Graha Kita 18 has a strategy where social media content is planned and published on a monthly basis. The social media content designed in Graha Kita 18 is based on two pillars of content, which is educational content and product knowledge to achieve audience and potentional customers reach out and awareness of Graha Kita 18 through social media.